Clinically relevant model of oxaliplatin‐induced sinusoidal obstruction syndrome. Issue 2 (6th October 2022) - Toda, Rei; Seo, Satoru; Uemoto, Yusuke; Morino, Koshiro; Nishino, Hiroto; Nakamura, Naohiko; Okuno, Masayuki; Iguchi, Kohta; Sato, Motohiko; Nakamura, Kojiro; Taura, Kojiro; Nakagawa, Shunsaku; et al.
Abstract: Aim: Sinusoidal obstruction syndrome (SOS) induced by oxaliplatin‐including chemotherapies (OXCx) is associated with impaired hepatic reserve and higher morbidity after hepatic resection. However, in the absence of an appropriate animal experimental model, little is known about its pathophysiology. This study aimed to establish a clinically relevant reproducible model of FOLFOX‐induced SOS and to compare the clinical/histopathological features between the clinical and animal SOS settings. Methods: We performed clinical/pathological analyses of colorectal liver metastasis (CRLM) patients who underwent hepatectomy with/without preoperative treatment of FOLFOX ( n  = 22/18). Male micro‐minipigs were treated with 50% of the standard human dosage of the FOLFOX regimen. Results: In contrast to the monocrotaline‐induced SOS model in rats, hepatomegaly, ascites, congestion, and coagulative necrosis of hepatocytes were absent in patients with CRLM with OXCx pretreatment and OXCx‐treated micro‐minipigs. In parallel to CRLM cases with OXCx pretreatment, OXCx‐challenged micro‐minipigs exhibited deteriorated indocyanine green clearance, morphological alteration of liver sinusoidal endothelial cells, and upregulated matrix metalloproteinase‐9. Using our novel porcine SOS model, we identified the hepatoprotective influence of recombinant human soluble thrombomodulin in OXCx‐SOS. Conclusions: With distinct differences between monocrotaline‐induced rat SOS and human/pig OXCx‐SOS, our pig OXCx‐SOS model serves as a preclinical platform for future investigations to dissect the pathophysiology of OXCx‐SOS and seek preventive strategies. Abstract : Sinusoidal obstruction syndrome (SOS) induced by oxaliplatin‐including chemotherapies (OXCx) is associated with impaired hepatic reserve and higher morbidity after hepatic resection; however, in the absence of an appropriate animal experimental model, little is known about its pathophysiology. In this study, we established a clinically relevant reproducible model of OXCx‐induced SOS and highlighted the disparities and common features between OXCx‐SOS and rodent monocrotaline induced SOS. With distinct differences between rodent monocrotaline‐SOS and human/pig OXCx‐SOS, our pig OXCx‐SOS model serves as a preclinical platform for future investigations to dissect the pathophysiology of OXCx‐SOS and seek preventive strategies.